INHIBITOR IN HEMOPHILIA - K Yantie, Veny; K, Ariawati (Medicina, 2012)
Hemophilia is an X-linked recessive disorder which is believed to affect approximately one in 5000-10.000 male birth. An inhibitor is a type of antibody. In hemophilia patients type A, B, and C are directly destroy factor VII, IX, and XI. The incidence of antibody development in hemophilia A is between 20% and 40%, hemophilia B inhibitors only 1 to 6 %. The presence of an inhibitor is usually confirmed using a specific blood test called the Bethesda inhibitor assay. The treatment of hemophilic bleeding in a person with an inhibitor can be a challenging experience. Patients hemophilia with inhibitor have poor prognostic. (MEDICINA 2012;43:31-36).